The Role of Educational Philosophy and Civic Education in Strengthening Students’ Integrity and Civic Responsibility - Yasmiati, Ni Luh Wayan; Lasmawan, I Wayan; Kertih, I Wayan; Suastra, I Wayan; Santosa, Made Hery (Universitas Muhammadiyah Mataram, 2026)
Integrity and civic responsibility are two crucial elements in the life of a nation and state. Both are widely believed to be developed through processes of awareness and education. Accordingly, this study aims to identify the role of educational philosophy, as a framework for cultivating awareness, and civic education in strengthening students’ integrity and civic responsibility. This research employed a sequential explanatory mixed-methods design, involving 22 respondents consisting of students, teachers, and school principals. The study began with the collection of quantitative data using a five-point Likert-scale questionnaire to identify the perceptions of students, teachers, and school principals regarding the role of educational philosophy and civic education in strengthening students’ integrity and civic responsibility. The collected data were quantified and analyzed quantitatively by calculating percentages and mean scores. Subsequently, qualitative data were gathered through interviews to confirm and elaborate on the previously obtained quantitative findings. The interview data were analyzed qualitatively using an interactive analysis model. The findings indicate that, in general, students, teachers, and school principals hold positive perceptions of the role of educational philosophy and civic education in strengthening students’ integrity and civic responsibility. This is reflected in the mean scores obtained from the questionnaire results, which show positive responses from students (4.52), teachers (4.57), and school principals (4.95). Furthermore, the qualitative findings support and reinforce the quantitative results. Therefore, it can be concluded that educational philosophy and civic education play a significant role in strengthening students’ integrity and civic responsibility.